Upaya Meningkatkan Hasil Belajar Materi Larutan Asam dan Basa Melalui Metode Project Based Learning Peserta Didik kelas XI MIPA 2 Tahun Pelajaran 2021/ 2022 - Ludovicus Agus Sri Mulyono (eductum: Jurnal Literasi Pendidikan, 2022)
The expected goal of this classroom action research is to improve the learning outcomes of students in class XI MIPA 2 SMA Negeri 1 Tengaran for the academic year 2021/2022 in the matter of solution acidity through the application of project based learning methods. This type of classroom action research uses 2 cycles. This research was conducted on students of class XI MIPA 2 SMA Negeri 1 Tengaran for the academic year 2021/2022. The number of students is 35 with 23 female students and 12 male students. The test and non-test instruments were applied with KKM 70. The learning outcomes of the affective, cognitive and psychomotor domains in cycle I and cycle II had increased. In the initial conditions, the average cognitive value acquisition was 53.7 with a category less than KKM (70). The results of the first cycle, the average value in the first cycle is 74.2 (low category) for the value of the affective domain, 67.9 (poor category) for the value of the cognitive domain, and 74.4 (enough category) for the value of the psychomotor domain. Results from cycle II. The average value obtained is 81.5 (high category) for the value of the affective domain, 82.2 (good category) for the value of the cognitive domain, and 83 (good category) for the value of the psychomotor domain. The conclusion of this study is that student learning outcomes increase after going through the application of the project based learning method.